2014
DOI: 10.3390/en7117794
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Performance of a Dual Loop Organic Rankine Cycle System for Waste Heat Recovery of a Heavy-Duty Compressed Natural Gas Engine

Abstract: A dual loop organic Rankine cycle (DORC) system is designed to recover waste heat from a heavy-duty compressed natural gas engine (CNGE), and the performance of the DORC-CNGE combined system is simulated and discussed. The DORC system includes high-temperature (HT) and low-temperature (LT) cycles. The HT cycle recovers energy from the exhaust gas emitted by the engine, whereas the LT cycle recovers energy from intake air, engine coolant, and the HT cycle working fluid in the preheater. The mathematical model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…They concluded that variations in engine rotational speed must be determined to evaluate the true performance of the combined system.Regarding ORC and stationary compressed natural gas (CNG) engines integration, two approaches have been studied: the use of multiple temperature loops for WHR from the engine intercooler, cooling system, and exhaust gases, and the use of single-temperature loops for WHR from engine exhaust. Within the first approach, Yao et al [12] were the first ones to propose an ORC system for WHR from the engine intercooler, exhaust gases, and cooling system by using a low and a high-temperature loop. Their ORC system used R245fa and achieved 10.8% thermal efficiency and 26.9 kW of power, which increased overall power production by 33.7%, keeping the same fuel consumption.…”
mentioning
confidence: 99%
“…They concluded that variations in engine rotational speed must be determined to evaluate the true performance of the combined system.Regarding ORC and stationary compressed natural gas (CNG) engines integration, two approaches have been studied: the use of multiple temperature loops for WHR from the engine intercooler, cooling system, and exhaust gases, and the use of single-temperature loops for WHR from engine exhaust. Within the first approach, Yao et al [12] were the first ones to propose an ORC system for WHR from the engine intercooler, exhaust gases, and cooling system by using a low and a high-temperature loop. Their ORC system used R245fa and achieved 10.8% thermal efficiency and 26.9 kW of power, which increased overall power production by 33.7%, keeping the same fuel consumption.…”
mentioning
confidence: 99%
“…While, engine coolant is a relative low grade waste heat, whose temperature is below 100 • C, but still significant due to the comparative amount of waste heat [2]. Using a thermodynamic cycle to generate extra power is a high-efficiency way among the technologies of E-WHR, mainly including single-loop organic Rankine cycle (ORC) [3,4], dual-loop ORC [5,6], steam Rankine cycle [7,8], CO 2 -based transcritical Rankine cycle (CTRC). Moreover, thermodynamic cycle is a feasible scheme to make a combined recovery of exhaust gas and engine coolant.…”
Section: Introductionmentioning
confidence: 99%
“…Their another related work estimated that ORCturbocompounding results in FCE improvements of 10% while maintaining the essential low NOx characteristics of ALPING combustion [14]. B. Yao [16]designed a dual loop organic Rankine cycle system for waste heat recovery of a heavy-duty compressed natural gas (CNG) engine, in which cycle R245fa was used as the working fluid. Together with B. Yao, S. Song et al [17] designed a set of ORC systems with internal heat exchanger to recover exhaust energy of a stationary compressed natural gas engine.…”
Section: Introductionmentioning
confidence: 99%
“…There are only a few works concerning about ORC combining natural gas engines [13][14][15][16][17]. K. K. Srinivasan et al [13] examined the EWH recovery potential from an advanced Low Pilot Ignited Natural Gas (ALPING) low temperature combustion using a bottoming ORC.…”
Section: Introductionmentioning
confidence: 99%